STRESS AND SMOKING AMONG UNIVERSITY STUDENTS AT THE UNIVERSITY OF THE WESTERN CAPE - Frantz, Jose (Journal of Community and Health Sciences, 2020)
Introduction: Stress is one of the most commonly reported reasons for smoking and generally smokers are perceived to experience more stress than non-smokers. Reducing stress may thus be an important part of smoking cessation. Objectives: The aim of the current study was to determine the prevalence of smoking and stress among university students attending the University of the Western Cape. Methods: A cross-sectional descriptive survey study design was used to describe and identify smoking habits of university students as well as their stress levels. The data was captured on Excel and SPSS was used to analyse the data. Participants: Nine hundred and twelve university students. Setting: Students enrolled at six faculties at the University of the Western Cape. Intervention: Self-answered questionnaire Results: Slightly more than half (53%) of the students had smoked previously but only, 61 % of these reported having smoked in the last month (current smokers). Females reported to experience more stress than males (stress score 21.6 vs 16.6). The main reasons for smoking included helping to relax, just enjoying smoking, coping with stress and smoking because friends smoke. Conclusion: Students need to know that increased stress levels are associated with smoking. Groups at higher risk are: those being older than 30 years; female; of the coloured ethnic group; in the fourth year of study and studying in the law faculty.